1990
DOI: 10.1144/gsl.sp.1990.055.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Carboniferous geology of the Southern North Sea Basin and controls on hydrocarbon prospectivity

Abstract: The thick sequences of Upper Palaeozoic strata present in the Southern North Sea Basin were probably deposited on a basement of Caledonian low-grade metamorphic rocks intruded by numerous late-Caledonian granitoids which form part of the subsurface extension of the Mid-European Caledonides linking the English Lake District and Northern Pennines to the Ardennes. This basement, along with the better known onshore areas of the British Isles and Ireland was intensely fragmented during late Devonian to mid-Carbonif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 16 publications
(9 reference statements)
1
42
0
Order By: Relevance
“…In several parts of northern England and in the southern North Sea, it has been suggested that deposition of the latest part of the basin-fill was contemporary with the early phases of the Variscan Orogeny and that many of the folds are in part syndepositional (e.g. Leeder & Hardman, 1990;Chadwick et al 1995, p. 36;Corfield et al 1996). Within the study area, Chadwick et al (1995, fig.…”
Section: Tectonic and Regional Settingmentioning
confidence: 90%
See 1 more Smart Citation
“…In several parts of northern England and in the southern North Sea, it has been suggested that deposition of the latest part of the basin-fill was contemporary with the early phases of the Variscan Orogeny and that many of the folds are in part syndepositional (e.g. Leeder & Hardman, 1990;Chadwick et al 1995, p. 36;Corfield et al 1996). Within the study area, Chadwick et al (1995, fig.…”
Section: Tectonic and Regional Settingmentioning
confidence: 90%
“…Murdoch and Ravenspurn anticlines), which formed as a result of late Carboniferous regional compressional tectonics (Leeder & Hardman, 1990). Besly, Burley & Turner (1993) suggested that the Ketch Formation formed contemporaneously with the evolving Variscan foreland basin, with sediment derived as a result of Variscan uplift.…”
Section: C Southern North Seamentioning
confidence: 99%
“…The Southern Permian Basin developed in response to crustal extension during initial stages of the break-up of Pangaea (Ziegler, 1988). The basin is characterised by east-west extension and some associated syn-depositional faulting has been speculated (Leeder and Hardman, 1990). This broad area of sediment accumulation stretched across much of northwest Europe towards modern-day Poland (Doornenbal and Stevenson, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Silver Pi{ Basin (with the Cleveland Basin) was the site of thick Namurian sedimentation (Leeder and Hardman 1990), with 2000 m of Namurian present in the central part. Deltaic deposits are found mainly on the southern flank of the Mid North Sea High and over the Proto-Inde Ridge.…”
Section: Regional Structure and Stratigraphymentioning
confidence: 99%